2020
DOI: 10.14341/probl12620
|View full text |Cite
|
Sign up to set email alerts
|

Role of leptin and nuclear receptor PPARγ in PCOS pathogenesis

Abstract: Polycystic ovary syndrome (PCOS) is the most common cause of female endocrine infertility. Insulin resistanсе is supposed to be one of the essential factors of this disease pathways. At the same time, the mechanisms of PCOS development in insulin-resistant patients have not been completely established. Leptin and Peroxisome Proliferator-Activated Receptor γ(PPARγ) are involved in carbohydrate metabolism and reproduction function regulation. It indicates that leptin and PPARγ possibly play a role in the pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…The copyright holder for this preprint this version posted January 4, 2023. ; https://doi.org/10.1101/2023.01.04.522712 doi: bioRxiv preprint patients (17). These studies suggest that ovarian fibrosis is related to the pathological changes of PCOS.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted January 4, 2023. ; https://doi.org/10.1101/2023.01.04.522712 doi: bioRxiv preprint patients (17). These studies suggest that ovarian fibrosis is related to the pathological changes of PCOS.…”
Section: Introductionmentioning
confidence: 84%
“…Studies have found that the expression of MMPs and TIMPs in PCOS is also unbalanced, which leads to abnormal deposition of ECM components such as collagen, resulting in ovulation disorders and polycystic changes in ovaries (1416). In addition, CTGF and PPARγ, extracellular matrix regulators were abnormally expressed in PCOS patients (17). These studies suggest that ovarian fibrosis is related to the pathological changes of PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that the expression of MMPs and TIMPs in PCOS is also unbalanced, which leads to the abnormal deposition of ECM components such as collagen, resulting in ovulation disorders and polycystic changes in ovaries [14][15][16]. In addition, CTGF and PPAR-γ extracellular matrix regulators were abnormally expressed in PCOS patients [17]. These studies suggest that ovarian fibrosis is related to the pathological changes of PCOS.…”
Section: Introductionmentioning
confidence: 90%